Net promoter score : satisfação, lealdade e rentabilidade do cliente - Valdez, António Alexandre Oliva Teles Travassos (2019)
Project Work presented as the partial requirement for obtaining a Master's degree in Statistics and Information Management, specialization in Marketing Research and CRM